Language variation and social class: Code switching in “My Fair Lady” - Indah Yana Aulia; Oktivia Hery Chandra (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2025)
This study aims to examine the relationship between language variation and social class through the phenomenon of code-switching in the film My Fair Lady. Language is positioned as a marker of social identity, where differences in dialect and speech patterns indicate the class stratification of the characters. The characters in this movie show linguistic differences that represent their class, such as the difference between upper-class and lower-class speech patterns. The purpose of this study is to analyze the role of code-switching in reflecting social class differences through the characters' language use. Data collection was conducted through a literature review using documentation techniques on the dialogue transcripts in the film. Furthermore, the data was analyzed qualitatively using a sociolinguistic and pragmatic approach to reveal the form and function of code-switching and the social context behind it. The results of the study show that code-switching is a linguistic strategy used by the main character to navigate and form a new social identity. Language, in this case, acts as a tool for social mobility as well as a mirror of prevailing class norms. This study contributes to sociolinguistic research, particularly in understanding the dynamics of language as a representation of symbolic power and class identity. Additionally, these findings are practically relevant in language education, especially in teaching language variation and social awareness in language use.